The Effect of Profitability, Leverage and Company Size on Financial Difficulties During Covid-19 And Post Covid-19 in the Oil and Gas Sector in the Period 2019-2023 - Marlina, Marlina; Hayat, Nurul; Sumarni, Sumarni (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The reason of this consider was to decide the impact of productivity, use and company measure on money related challenges. The inquire about strategy may be a causality approach. Purposive inspecting was utilized to choose the test. Purposive examining was utilized to choose 60 oil and gas companiess recorded on the IDX between 2019 and 2023 based on 300 monetary articulation information. Stata/IC 15 was utilized to prepare the investigate information, which came from the Osiris and Bloomberg databases. The discoveries of the consider uncover that productivity plays a critical and positive part in easing money related trouble amid and after the COVID-19 widespread. Be that as it may, the relationship between productivity and money related trouble developed after the pandemic, suggesting that beneficial businesses are still vulnerable to budgetary trouble. Within the in the mean time, amid the COVID-19 plague, use has no perceivable affect on budgetary enduring. Use, on the other hand, essentially declines money related hopelessness after the widespread, showing that a rise in use really reduces money related trouble taking after the widespread. Amid the COVID-19 widespread, firm estimate essentially emphatically influences money related hardship; the larger the firm, the more noteworthy the probability of encountering budgetary inconvenience. Firm estimate, in any case, now not altogether influences monetary enduring amid the plague